1989
DOI: 10.1111/j.1751-1097.1989.tb09195.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical Urocanic Acid Enhances Uv‐induced Tumour Yield and Malignancy in the Hairless Mouse

Abstract: Epidermal urocanic acid has been postulated to be the mediator of the specific state of immunosuppression induced by UV irradiation, by which UV-initiated tumour cells are able to evade normal recognition and can survive to grow progressively into malignant tumours. These experiments demonstrate that topical application of UV-irradiated urocanic acid systemically suppresses the contact type hypersensitivity response to oxazolone in hairless mice. In addition, topically applied urocanic acid markedly increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 22 publications
0
43
0
Order By: Relevance
“…The inhibitory effect of cis-UCA on tumor Ag presentation by LC as well as the elevated concentrations of cis-UCA within the skin after UV treatment (13,34) suggest that cis-UCA may play a role in the development of UV-induced skin cancer. Accordingly, topical application of UCA, followed by chronic UVB exposure resulted in augmented skin tumor development (12). These data clearly indicated that cis-UCA can promote photocarcinogenesis.…”
Section: Neutralization Of Endogenous Cis-uca By Anti-cis-uca Ab Treamentioning
confidence: 71%
See 1 more Smart Citation
“…The inhibitory effect of cis-UCA on tumor Ag presentation by LC as well as the elevated concentrations of cis-UCA within the skin after UV treatment (13,34) suggest that cis-UCA may play a role in the development of UV-induced skin cancer. Accordingly, topical application of UCA, followed by chronic UVB exposure resulted in augmented skin tumor development (12). These data clearly indicated that cis-UCA can promote photocarcinogenesis.…”
Section: Neutralization Of Endogenous Cis-uca By Anti-cis-uca Ab Treamentioning
confidence: 71%
“…In addition, systemic application of cis-UCA prolonged allograft survival in mice (11). Topically applied trans-UCA in combination with chronic UVR treatment resulted in enhanced photocarcinogenesis in mice, indicating that cis-UCA may be involved in the generation of UV-induced skin cancer probably by causing immunosuppression (12). To this end, previous investigations by our group have shown that cis-but not trans-UCA inhibits the ability of Langerhans cells (LC), the primary APC in the skin, to present tumor Ag (TA), both for the induction and elicitation of antitumoral immune responses in mice (13).…”
mentioning
confidence: 99%
“…In previous studies, mice were unrestrained as they underwent whole-body irradiation with UVB [24,33]. In those types of experimental conditions, each animal could be irradiated with different doses of UVB, which might contribute to the large experimental errors.…”
Section: Discussionmentioning
confidence: 99%
“…The photon energy absorbed by UCA is effectively dissipated through the reversible isomerization to cis-urocanic acid [21,22]. However, UCA's reputation as an ideal natural sunscreen was shattered by the observations that cis-urocanic acid mediated the immunosuppressive effect of UV [23], and UCA increased the photocarcinogenic risk in hairless mice [24]. In contrast, Barresi and colleagues observed that histidase-deficient mice were more susceptible to UV-induced DNA damage and apoptosis than wild type mice [25].…”
Section: Introductionmentioning
confidence: 99%
“…It does not, however, inhibit mitogen-induced lymphocyte transformation (47). Additionally, topical cis-UCA treatment enhances UVR-induced tumor yield in hairless mice (48). This area is complicated, however, by the recent report that exposure of mice to UVA I1 ( 3 6 0 4 0 0 nm) radiation produces as much cis-UCA in the epidermis as UVB radiation but does not lead to suppression of DTH (49).…”
Section: Photoreceptors For Uvr-induced Immunsuppressionmentioning
confidence: 77%